Case report: Idiopathic pulmonary fibrosis induced by nab-paclitaxel: A rare complication - Shen, Jiahui; Wen, Zhongyong; Lin, Jingxia; Su, Huiwen (Frontiers in Pharmacology, 2023)
Background: Ovarian cancer (OC) is one of the deadliest gynaecological cancers, with the most advanced disease and poor survival. Although BRCA genes play a crucial role in maintaining genomic stability and offer the possibility of individualized treatment in the clinic, as new and more appropriate treatment options emerge, recent treatment-related adverse events (TRAEs) are challenges and difficulties clinicians face. Case Presentation: An 80-year-old woman was diagnosed with stage IIIC ovarian high-grade serous adenocarcinoma (CT3cN1MX) with BRCA2 as the causative gene and received three courses of neoadjuvant chemotherapy (nab-paclitaxel 400 mg + carboplatin 450 mg) before surgery. Chest CT before chemotherapy showed interstitial pneumonia(IIPs). During chemotherapy, there were four times of coughs with white sticky phlegm and shortness of breath; after three times of chemotherapy, myelosuppression occurred. After three sessions of empirical cough and phlegm relieving, oxygen inhalation, corticosteroids, anti-infection and leukocytosis treatment, the symptoms were intermittent and gradually aggravated. Idiopathic pulmonary fibrosis (IPF) was diagnosed one week after the third chemotherapy. After high-dose corticosteroids and nintedanib anti-fibrosis, the pulmonary symptoms were relieved, and intermediate tumour cytoreduction was performed. After receiving nab-paclitaxel 400mg single-agent chemotherapy combined with nintedanib for anti-fibrosis, the pulmonary symptoms were significantly reduced, and the patient obtained an excellent treatment response. Conclusion: This is the first case report of IPF as a TRAE with nab-paclitaxel in OC patients and is extremely rare. It is hoped that in the course of treatment, it is necessary to maintain a high degree of vigilance for patients with interstitial pneumonia and to attract the attention of clinicians to improve the safety of the medication. Early diagnosis and early antifibrotic therapy can reverse lung damage.